An analytical approach to the accounting of settlement lands: A case study of Mirishkor District - Nartoshevich, Aliqulov G‘olib; Qizi, Toshpo’latova Zebiniso Abbos; O‘g‘li, Nortoshov Asilbek G‘olib (Goodwood Publishing, 2025)
Purpose: This study aimed to analyze the legal, technical, and organizational aspects of accounting for settlement lands in the Mirishkor district. It focuses on how settlement lands are classified, distributed, and managed, while also identifying the current challenges in maintaining accurate and reliable land records that support sustainable development. Research Methodology: This study applied a combination of geostatistical analysis, geospatial object mapping, remote sensing, cartographic tools, and algorithmic approaches. These methods are employed to evaluate patterns of land-use distribution, monitor settlement expansion, and propose improvements to land accounting systems. Results: The results show that the Mirishkor district consists of 16,359 household plots with a total of 4,494 ha, averaging 0.27 ha per plot. Of this area, 797 hectares are occupied by residential buildings. The findings reveal significant pressure on land allocation and highlight the need for more accurate monitoring and systematic classification of settlement land. Conclusions: This study concludes that adopting a unified geospatial cadastral system, updating the address registry, and digitizing land accounting processes will improve efficiency, transparency, and sustainability in land management. Limitations: This research is limited to the Mirishkor district; thus, the findings cannot be generalized to other regions with different demographic, geographic, or legal conditions. Furthermore, reliance on cadastral and statistical data may not capture informal or rapidly changing settlement patterns in these areas.